Вплив металевих домiшок на транспортнi властивостi багатокомпонентної плазми пiдводних розрядiв - Porytskyy, P. V.; Starchyk, P. D. (Publishing house "Academperiodika", 2019)
The influence of metal impurities on the transport properties of multicomponent thermal plasma at the ambient atmosphere of water vapor has been considered. The calculations are carried out on the basis of the Grad method. It is shown that a small amount of metal impurities can substantially change the magnitude of transport coefficients in comparison with the case of pure water vapor. The influence of the model for the cross-section of electron collisions with a metal atom on the transport properties of thermal plasma is analyzed.